Youth empowerment against poverty in Yobe State, Northern Nigeria - Alhaji Ahmadu Ibrahim; Julius Kiiza; Peter Atekyereza (Universitas Muhammadiyah Malang, 2023)
Global efforts to end poverty and unfair development should focus on the empowered youth as the cornerstone. In Nigeria, the youth form 60 percent of the population. The majority of them are unemployed and ultimately poor. Poverty reduction requires empowerment to overcome the barriers to a better life. This study examined the nature of youth empowerment and its impact on the well-being of the youth in Yobe State, Nigeria. It used a quantitative method and administered questionnaires to 393 randomly selected respondents. Data was collected on youth's attitudes, views and experiences on various aspects of their lives and well-being and the nature of empowerment programmes in Yobe State. The study findings show that many empowerment programmes have been implemented but have had low impact on the youth. Poverty and unemployment remain high, mainly among the youth. In addition, youth attitudes and experiences show a lack of satisfaction with the nature of youth empowerment. Disempowered youth lack the confidence and belief that they have the opportunities to develop themselves or escape poverty and such disempowerment compromises their citizenry roles as the youth. Therefore, there is a need to improve the infrastructure and strengthen empowerment programmes to improve the well-being of the youth.